Efficient micropropagation of french tarragon (artemisia dracunculus l.) (2012)
French tarragon is cultivated in Colombia for exportation. According to French tarragon producers, crops should be renovated but traditional propagation with cuttings has a high percentage of loss and there is incidence of Colombian tarragon crop rust. An alternative for inducing juvenile characteristics and increasing percentages of rooting and clean plant propagation material is micropropagation. The aim of this research was to generate an efficient micropropagation protocol, which would be useful for providing clean propagation plant material and contributing to the renovation of French tarragon crops in Colombia. For establishment, the effect of both type and concentration of gelling agents and liquid mediums was assessed. For multiplication and rooting, the effect of indole acetic acid (IAA), N6-furfuril amine purine, planting orientation and pinching was assessed. Although French tarragon showed susceptibility to hyperhydricity, it was possible to determine protocols from 1 mm-meristematic tips established in the liquid medium Murashige and Skoog (MS), with in vitro multiplication/ rooted in a solid medium MS supplemented with IAA 0.1 mg L-1. Additionally, an alternative multiplication protocol was assessed from propagules horizontally sown in a solid medium MS supplemented with KIN 0.5 mg L-1 and AIA 5 mg L-1.